SALVE MADRINHA - GIMENES, MIRIAM (2019)
SAMBISTA BETH CARVALHO, QUE ESTAVA INTERNADA DESDE JANEIRO, MORRE AOS 72 ANOS
PORTUGUES
Keywords: SAMBA; MUSICA BRASILEIRA; SAMBISTAS; CARVALHO, BETH; WWW.DGABC.COM.BR; ARTIGO